2010
DOI: 10.1016/j.gloplacha.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

A speleothem record of glacial (25–11.6 kyr BP) rapid climatic changes from northern Iberian Peninsula

Abstract: Keywords: speleothems northern Iberian Peninsula Marine Isotope Stage 2 last deglaciation stable isotopes trace elements rapid climate change Low and high frequency climatic fluctuations in northern Iberian Peninsula during the last glacial maximum (LGM) and deglaciation are documented in a stalagmite using δ 18 O and δ 13 C and hydrologically sensitive trace metal ratios Mg/Ca and Ba/Ca. U/Th dating indicates speleothem growth commenced at 25 kyr BP (Present = year 1950) and extended to 11.6 kyr BP making thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
117
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(144 citation statements)
references
References 75 publications
20
117
1
6
Order By: Relevance
“…This phase could therefore be correlated with the late glacial interstadial GI-1 (Bolling-Allerad, 14,700-12,650calyrBP; Bjorcketal., 1998), which is characterized by a significant rise in temperature and precipitation (Clark et al, 2012). In northern Iberia, the speleothem record from El Pindal Cave indicates that this warming was gradual and precipitation only reached significant amounts near the end of the period (Moreno et al, 2010), while chironomid-based July air temperature from La Roya shows a rise of 2.5°C at the beginning of the interstadial and a decreasing trend afterwards (Munoz Sobrino et al, 2013). The spread of pioneer trees detected in Ayoo was very slight and late compared to other records from the Northwestern Iberian Mountains, where pine and birch woodlands became well-developed, and an expansion of relatively thermophilous trees, such as oaks, took place (Maldonado, 1994;Allen et al, 1996;van der Knaap and van Leeuwen, 1997;Munoz Sobrino et al, 2007).…”
Section: The Landscapes Of the Northern Iberian Plateau During The Lamentioning
confidence: 99%
“…This phase could therefore be correlated with the late glacial interstadial GI-1 (Bolling-Allerad, 14,700-12,650calyrBP; Bjorcketal., 1998), which is characterized by a significant rise in temperature and precipitation (Clark et al, 2012). In northern Iberia, the speleothem record from El Pindal Cave indicates that this warming was gradual and precipitation only reached significant amounts near the end of the period (Moreno et al, 2010), while chironomid-based July air temperature from La Roya shows a rise of 2.5°C at the beginning of the interstadial and a decreasing trend afterwards (Munoz Sobrino et al, 2013). The spread of pioneer trees detected in Ayoo was very slight and late compared to other records from the Northwestern Iberian Mountains, where pine and birch woodlands became well-developed, and an expansion of relatively thermophilous trees, such as oaks, took place (Maldonado, 1994;Allen et al, 1996;van der Knaap and van Leeuwen, 1997;Munoz Sobrino et al, 2007).…”
Section: The Landscapes Of the Northern Iberian Plateau During The Lamentioning
confidence: 99%
“…Based on U-Th and 14 C dating, and X-ray diffraction of submerged speleothems, Surić and Juračić (2010) have partially constructed curve of relative sea-level changes during the last 220 ka for the Eastern Adriatic coast which generally corresponds to the global sea-level curve. Their studies proposed that environmental settings along eastern Adriatic varied due to climate changes, and that environmental conditions were favorable for karstification and speleothem deposition even during the Last Glacial Maximum, as in the Eastern Mediterranean region (Bar-Matthews et al 2003) and unlike in large part of northern Europe (Gascoyne 1992;Lowe & Walker 1998;Genty et al 2006; EARLy AND MID-HOLOCENE ENVIRONMENTAL CONDITIONS IN THE EASTERN ADRIATIC RECORDED IN SPELEOTHEMS ... Moreno et al 2010). The recent studies of Croatian speleothems (Lončar 2012) have showed that their isotopic composition records the period from the Upper Pleistocene (MIS 5) to the Upper Holocene (MIS 1), showing frequent fluctuations and abrupt changes in stable isotope values along with numerous interruptions in growth.…”
Section: Introductionmentioning
confidence: 99%
“…In central Europe, hydrogen isotope ratios of land plant-derived lipid biomarkers from Meerfelder Maar confirm that North Atlantic atmospheric cooling began at ∼ 12.880 ka BP (Rach et al, 2014), synchronous with both the onset of Greenland GS-1-related cooling and the LSE but preceding the atmospheric response associated with meridionally displaced westerly winds at the same site (importantly, in Meerfelder Maar (MFM) the first data point suggesting cooling occurs immediately above the LST; Rach et al, 2014). This observation is further supported by speleothem δ 18 O records from the La Garma and El Pindal caves in northern Spain (Baldini et al, 2015b;Moreno et al, 2010), Swiss lake sediment δ 18 O records (Lotter et al, 1992), Lithuanian lake sediment trace element profiles , and Swiss lake organic molecule-based (BIT and TEX 86 ) temperature reconstructions (Blaga et al, 2013), all showing North Atlantic cooling beginning immediately after the LSE (Fig. 4).…”
Section: The Timing Of the Laacher See Eruption Relative To The Youngmentioning
confidence: 56%